World TB Day 2024 - DR. SAULAT ULLAH KHAN, (Pakistan Journal of Medical & Health Sciences, 2024)
World TB day, falling on 24th March each year, is designed to build public awareness that tuberculosis still remains a public health problem in much of the world, causing the death of more than a million people each year, mostly in the third world. Dr. Robert Koch astounded the scientific community on 24th March 1882 by announcing that he had discovered the cause of tuberculosis, the TB bacillus. Koch's discovery opened the way towards diagnosing and curing tuberculosis. Everyone can take an active role in helping all people in need gain access to accurate TB diagnosis and effective treatment. Patient can stop TB by becoming active participant in their own care and taking all their anti-TB drugs as prescribed. Health workers can stop TB by staying alert to the symptoms of the disease and providing prompt diagnosis and treatment. Scientist can stop TB by engaging in need research to develop new diagnostics, new drugs and new vaccines. Teachers can stop TB by educating their students about this age-old scourge. Communities can stop TB by sharing information to help prevent the disease and get treatment to those who need it.